D-dimer as a diagnostic tool for canine thromboembolic disorders - GIANNOULOPOULOS (Γ.Δ. ΓΙΑΝΝΟΥΛΟΠΟΥΛΟΣ), G. D.; ATHANASIOU (Λ.Β. ΑΘΑΝΑΣΙΟΥ), L. V.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
D-dimers are small protein fragments present in the blood after a blood clot is degraded by plasmin. During the fibrin(ogen) degradation, a number of products are produced called fibrin(ogen) degradation products (FDPs). D-dimers are part of the FDPs, formed as a result of plasmin activity on cross-linked fibrin. Thus, D-dimers indicate the activity of both thrombin and plasmin and are specific markers for fibrinolysis. D-dimer measurement is widely used in the diagnostic work-up of human patients as the most sensitive test to diagnose pulmonary thromboembolism (PTE) and disseminated intravascular coagulation (DIC) and it is, also, considered essential in the evaluation of antithrombotic therapy. During the last decade, there was considerable research regarding the potential utility of D-dimer in veterinary medicine, particularly in canine and equine species. In dogs, D-dimer plasma concentrations can be used to rapidly detect the thrombotic complications and DIC associated with many systemic diseases (high quantitative D-dimer levels). The symptoms of PTE are subtle and the confirmation of diagnosis with routine hematological tests can be difficult, thus jeopardizing the patient's survival. Several techniques have been employed for the detection of D-dimer; the immunoenzymatic assay (ELISA), the immuno-turbidimetric assay and several latex agglutination assays are more commonly used.